[Book Review] Ulrich Koester: Foundations of agricultural market analysis and agricultural policy - Thomas Glauben (Journal of New Economy, 2021)
The article provides an overview of the main contents of a brand new textbook on agricultural economics and evaluates them in the context of economic theories and concepts as well as against the background of agricultural developments. In addition, the second part of the article presents an outstanding contribution of the author of the textbook to agricultural research and teaching.
Keywords: 330; agricultural market; policy analysis; instruments of agricultural policy; European Union; price formation